Dye‐Sensitized Solar Cells: Substituting TiCl4–Carbon Nanohorn Interfaces for Dye‐Sensitized Solar Cells (Adv. Energy Mater. 6/2014). Issue 6 (April 2014) - Casillas, Rubén; Lodermeyer, Fabian; Costa, Rubén D.; Prato, Maurizio; Guldi, Dirk M.
<x xml:space="preserve">Abstract</x> A strategy to introduce semiconducting and mesoporous carbon nanohorns as interlayers in the photoelectrodes of dye‐sensitized solar cells, without affecting the overall performance, is reported by Dirk M. Guldi and co‐workers in article number 1301577. This provides an easy, clean, and ecofriendly alternative to achieve highefficiency solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>